2014
DOI: 10.1159/000367895
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Recovery in Patients with Anorexia Nervosa: The Importance of Insulin-Like Growth Factor 1

Abstract: Background: Follow-up visits of patients recovering from anorexia nervosa (AN) have shown that some patients do not resume menstrual cycles despite returning to the normal weight for their age and height. Aim: To verify whether leptin, insulin-like growth factor 1 (IGF-1) or another hormonal marker could be a good predictor of the return of menses. Patients and Methods: This prospective study included female adolescents diagnosed with AN or eating disorders not otherwise specified (EDNOS) and who were being tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Estrogen: The association between estrogens and female weight has been previously reported (Leeners et al 2017). An increase in estradiol levels resulting from follicular maturation and conversion of androgens to estrogens in fat tissue (associated with weight gain) is confirmed in all of the studies investigating hormonal levels in resumption of menses (Arimura et al 2010;Audi et al 1998;Barakat et al 2016;Cominato et al 2014;Holtkamp et al 2003;Jacoangeli et al 2006;Karountzos et al 2017;Pitts et al 2014;Tokatly Latzer et al 2019). Estrogen increases GnRH receptor gene expression and enhances the ability of FSH to induce expression of LH receptors and promote follicular growth (Turzillo, Nolan, and Nett 1998;Richards et al 1976).…”
Section: Medicationmentioning
confidence: 86%
See 1 more Smart Citation
“…Estrogen: The association between estrogens and female weight has been previously reported (Leeners et al 2017). An increase in estradiol levels resulting from follicular maturation and conversion of androgens to estrogens in fat tissue (associated with weight gain) is confirmed in all of the studies investigating hormonal levels in resumption of menses (Arimura et al 2010;Audi et al 1998;Barakat et al 2016;Cominato et al 2014;Holtkamp et al 2003;Jacoangeli et al 2006;Karountzos et al 2017;Pitts et al 2014;Tokatly Latzer et al 2019). Estrogen increases GnRH receptor gene expression and enhances the ability of FSH to induce expression of LH receptors and promote follicular growth (Turzillo, Nolan, and Nett 1998;Richards et al 1976).…”
Section: Medicationmentioning
confidence: 86%
“…Similarly, levels of growth hormone and insulin-growth factor-1 (IGF1) are reduced in FHA (Bomba et al 2007;Miller et al 2004). An IGF-1 level of >342.8 ng/ml has been proposed to be a predictor for return of menses (Cominato et al 2014), although two other studies have found no positive correlation (Falsetti et al 2002;Arimura et al 2010).…”
Section: Body Weight and Energy Availabilitymentioning
confidence: 99%
“…Although self‐reported weight and menstrual status history in adolescent ED populations are highly accurate (Swenne, Belfrage, Thurfjell, & Engström, ), this accuracy has not been established in adults. Further, menstrual function is one marker of physiological health, but we did not assess other physiological variables (e.g., hormones, body fat percentage) that are associated with menses resumption (Arimura et al, ; Cominato et al, ; El Ghoch, Calugi, Chignola, Bazzani, & Grave, ; Pitts, Blood, Divasta, & Gordon, ) and may be helpful indicators of remission. Menses resumption also does not necessarily correspond with stable menstrual recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, we found an inverse correlation of fT3 with the amount of weight loss and a positive correlation between fT3 and leptin levels, as previously described [ 36 ]. But in addition, here we observed a highly significant positive correlation between fT3 and estradiol, with fT3 levels tending to an earlier normalization before resumption of menses and rise of circulating estradiol in Group 0, thus indicating fT3 rise as an early marker of the resumption of hypothalamic activity.This adds to the evidence already available for IGF1 [ 37 ] as opposed to cortisol levels which are reported to be a predictor of hypothalamic inhibition [ 38 ]. Still, the usefulness of fT3 levels in this setting should always be put in context of clinical parameters.…”
Section: Discussionmentioning
confidence: 69%